Development of GaN substrate with a large diameter and small orientation deviation. Issue 8 (6th February 2017) - Yoshida, Takehiro; Imanishi, Masayuki; Kitamura, Toshio; Otaka, Kenji; Imade, Mamoru; Shibata, Masatomo; Mori, Yusuke
Abstract : In this study, we demonstrated a very large freestanding GaN crystal with a diameter of 175 mm developed by the "tiling technique". The technique merges small multiple seed wafers with a thick GaN layer grown by hydride vapor phase epitaxy. To the best of our knowledge, it is the largest GaN crystal ever reported. Its orientation deviation could be the same as those of applied individual seeds by using the starting substrate, which was prepared by binding all the seeds on a base plate with a high temperature adhesive. Scrupulous attention was required to select the materials. Furthermore, we were able to grow GaN with hydride vapor phase epitaxy on a high‐quality GaN substrate, which was prepared by an Na‐flux method, with no crystal deteriorations. Through the fusion of the above results, the ideal GaN substrates can be realized. Example of a freestanding GaN crystal with a diameter of 175 mm developed by the "tiling technique".